235k views
3 votes
Find the LCM of these two expressions: m2 + 11m + 10 and m2 + 9m – 10.

User SoWeLie
by
5.1k points

2 Answers

3 votes

Answer:

Sample Answer

Explanation:

Find the LCM of these two expressions: m2 + 11m + 10 and m2 + 9m – 10.-example-1
User Wsn
by
5.5k points
7 votes

Answer:

(m-1)(m+1)(m+10)

Explanation:

Factors of each expression:

  • m² + 11m + 10 =
  • m²+m + 10m+10 =
  • m(m+1)+10(m+1) =
  • (m+1)(m+10)

m² + 11m + 10 = (m+1)(m+10)

  • m² + 9m – 10 =
  • m² - m + 10m - 10 =
  • m(m-1) + 10(m-1) =
  • (m-1)(m+10)

m² + 9m – 10 = (m-1)(m+10)

LCM of the two expressions is:

  • (m-1)(m+1)(m+10)

User Gerrie
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.